The ghost of institutions past: History as an obstacle to fighting tax evasion - Aaron Kamm; Christian Koch; Nikos Nikiforakis (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
If taxpayers believe past rates of compliance are indicative of the future, traditional measures for combating tax evasion can be compromised. We present evidence from a novel laboratory experiment with strategic complementarities showing that a history of low compliance can render a major institutional reform ineffective at reducing tax evasion. The experimental treatments manipulate the history of tax compliance by varying the percentage of tax revenue embezzled by a `politician' – our measure of `institutional quality'. We show that tax compliance is substantially higher in good-quality than bad-quality institutions when there is no history of tax evasion. When a bad-quality institution is replaced with a good-quality one, however, tax compliance remains low, as if the institutional change had not occurred. The reason is that the institutional change leaves expectations about future compliance largely unaffected. A history of high-quality institutions, on the other hand, shields tax compliance only partly from institutional deterioration. We discuss reasons for this, policy implications of our findings and evidence that a society-wide poll can assist in overcoming the `ghost of institutions past'.
Keywords: C92; H26; 330; tax evasion; interdependence; multiple equilibria; path dependence; experiment